Answer:
[tex]\mathbf{\int \int _R \ 4xy e^{x^2 \ y} \ dA = 2 (e^7 -8)}[/tex]
Step-by-step explanation:
Given that:
[tex]\int \int _R 4xye^{x^2 \ y} \ dA, R = [0,1]\times [0,7][/tex]
The rectangle R = [0,1] × [0,7]
R = { (x,y): x ∈ [0,1] and y ∈ [0,7] }
R = { (x,y): 0 ≤ x ≤ 1 and 0 ≤ x ≤ 7 }
[tex]\int \int _R \ 4xy e^{x^2 \ y} \ dA = \int^{7}_{0}\int^{1}_{0} 4xye^{x^2 \ y} \ dx dy[/tex]
[tex]\int \int _R \ 4xy e^{x^2 \ y} \ dA = \int^{7}_{0} \begin {bmatrix} ye^{yx^2} \dfrac{4}{2y} \end {bmatrix}^1 _ 0 \ dy[/tex]
[tex]\int \int _R \ 4xy e^{x^2 \ y} \ dA = \int^{7}_{0} \begin {bmatrix} ye^{y1^2} \dfrac{4}{2y} - ye^{y0^2} \dfrac{4}{2y} \end {bmatrix}\ dy[/tex]
[tex]\int \int _R \ 4xy e^{x^2 \ y} \ dA = \int^{7}_{0} \dfrac{4}{2}(e^y -1) \ dy[/tex]
[tex]\int \int _R \ 4xy e^{x^2 \ y} \ dA = \dfrac{4}{2}[e^y -1]^7_0 \ dy[/tex]
[tex]\int \int _R \ 4xy e^{x^2 \ y} \ dA = 2 [(e^7 -7)-(e^0 -0)][/tex]
[tex]\int \int _R \ 4xy e^{x^2 \ y} \ dA = 2 [(e^7 -7)-1][/tex]
[tex]\mathbf{\int \int _R \ 4xy e^{x^2 \ y} \ dA = 2 (e^7 -8)}[/tex]